The imposition of an increased environmental fee for operating without a required permit or another administrative decision, and the cause of the absence of the permit or decision - Szuma, Karolina (Polish Yearbook of Environmental Law, 2014)
As long as the applicant files an application for a new permit well in advance, before the expiry of the existing permit, and allowing enough time for the application to be processed, and the new permit is not issued before the expiry of the existing one because of reasons attributable to the administrative body (such as its inaction or tardy proceedings), the issuance of a decision, referred to in article 193 section 4 EPA, is relevant for the holder of the existing permit. What follows is that the environmental fee should be paid at the rate applicable during the period of the previous permit from the moment of its expiry until the new one is obtained. It may therefore be found inadmissible to make an entity liable for the tardiness of administrative proceedings by imposing on it the increased environmental fees.